The transformation of the protagonist’s personality in the tragedy of king lear (2010)
When Bloom (1998) claims that Shakespeare invented our sense of personality, he appears to be chiefly referring to a characteristic inwardness which underlies a constant process of personal change that finds in Shakespearean characters not only its first dramatic representation but also its most comprehensive one. We may add something more to Bloom’s appreciation and say that all Shakespearean characters are not just individually different from each other, having their own particular personality traits, but also exhibit a range of different personalities within their personalities as they fulfil roles as parents, siblings, spouses, rulers and subjects. It is not difficult to observe that such roles would immediately imply relationships between characters and, in this way, the aforementioned inwardness is enriched and balanced with a constant presence of the other as the alternative force behind dramatic action.